Handbook of Psychology, Second Edition 2012
DOI: 10.1002/9781118133880.hop212001
|View full text |Cite
|
Sign up to set email alerts
|

A Snapshot in Time: Industrial–Organizational Psychology Today

Abstract: I" VERSUS "O" TENSION 3 PSYCHOLOGY VERSUS BUSINESS TENSION 4 SCIENCE VERSUS PRACTICE TENSION 5 CONCLUSION 12 REFERENCES 12As we write this chapter, the field of industrialorganizational psychology in the United States has survived its third attempt at a name change. To provide a little perspective, the moniker industrial psychology became popular after World War I, and described a field that was characterized by ability testing and vocational assessment (Koppes, 2003). The current label, industrialorganization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…It is clear that the lack of such publications is not because of a lack of interest. For perspective, a topical examination of presentations at the 2011 Society for Industrial and Organizational Psychology annual conference (Highhouse & Schmitt, 2012) revealed that diversity was third (tied with personality) behind only testing/assessment and leadership. Likewise, a similar examination of organizational behavior-related submissions to the Academy of Management Journal (AMJ) from 2007 to 2009 (Morrison, 2010) revealed that diversity was third behind only leadership and teams, suggesting any underrepresentation in top journals is probably not simply a "pipeline" issue.…”
Section: Preliminary Evidence Of Subtle Bias Against Diversity Scholarshipmentioning
confidence: 99%
“…It is clear that the lack of such publications is not because of a lack of interest. For perspective, a topical examination of presentations at the 2011 Society for Industrial and Organizational Psychology annual conference (Highhouse & Schmitt, 2012) revealed that diversity was third (tied with personality) behind only testing/assessment and leadership. Likewise, a similar examination of organizational behavior-related submissions to the Academy of Management Journal (AMJ) from 2007 to 2009 (Morrison, 2010) revealed that diversity was third behind only leadership and teams, suggesting any underrepresentation in top journals is probably not simply a "pipeline" issue.…”
Section: Preliminary Evidence Of Subtle Bias Against Diversity Scholarshipmentioning
confidence: 99%
“…These issues will likely never get addressed if I/o psychologists address concerns only directly relevant to organizations. A similar more extended discussion of this concern is available in Highhouse and Schmitt (2012). The next section of this chapter details some of these issues.…”
Section: Limitations Of Organizational Collaborationsmentioning
confidence: 93%
“…Esta alineación de la formación en psicología al campo administrativo tradicional, conlleva una dicultad para interpelar a los profesionales de la psicología organizacional a buscar un equilibrio para atender los intereses productivos de la organización, sin olvidar que las personas que la componen también tienen necesidades de bienestar y no son meros recursos humanos (Highhouse & Schmitt, 2013). La interpelación a fomentar prácticas organizacionales más humanas y críticas exige que la formación universitaria en psicología organizacional brinde una visión de carácter crítico y socialmente responsable, para que los psicólogos integren dos roles o escenarios, aparentemente separados, que suelen confrontar la integridad de su ejercicio profesional: por un lado, el rol cientíco enfocado en el desarrollo de teorías que básicamente se queda en los alcances del ámbito académico; por otro lado, se reconoce el rol profesional práctico, dedicado a la solución de problemas de la vida real organizacional que, en muchos casos, opera desde el sentido común (Carvajal, Ulloa, & Morales, 2007;Pulido-Martínez, 2004;Pulido-Martinez & Jaraba, 2017).…”
Section: El Desafío a La Formación En Psicología Organizacional Localunclassified